2008
DOI: 10.1007/s12149-007-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual-time-point FDG-PET for evaluation of lymph node metastasis in patients with non-small-cell lung cancer

Abstract: Dual-time-point FDG-PET (combined delayed PET and RI) showed better (although not statistically significant) specificity, positive predictive value, and accuracy than early or delayed PET alone for lymph node staging in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 15 publications
0
33
1
1
Order By: Relevance
“…DTPI has been considered helpful for the discrimination of benign and malignant disease, and the staging of lymph node status in patients with pulmonary malignancy [6][7][8]. As regards our cases, DTPI may be also useful for showing the description of metabolic status and the extent of benign infectious disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTPI has been considered helpful for the discrimination of benign and malignant disease, and the staging of lymph node status in patients with pulmonary malignancy [6][7][8]. As regards our cases, DTPI may be also useful for showing the description of metabolic status and the extent of benign infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…If one adopts the criterion that more than a 10% increase of standardized uptake value (SUV) between the initial and delayed scan signals malignancy, significant improvement in the diagnostic accuracy for the detection of malignant pulmonary nodules has been observed [7]. DTPI has also been applied to stage lymph node status in patients with pulmonary malignancy, and DTPI showed better specificity, positive predictive value and accuracy [8].…”
Section: Introductionmentioning
confidence: 99%
“…The primary tumour and lymph nodes that were .1.0 cm in short axis or PET positive were delineated as the gross target volume (GTV) or ITV. The positive lymph nodes were diagnosed in consultation with the nuclear medicine physician [12].…”
Section: Treatment Procedures Of Radiation Therapymentioning
confidence: 99%
“…Nishiyama et al also evaluated the diagnostic performance of DTP PET/CT for the diagnosis of LN metastasis in patients with NSCLC. They reported that DTP PET showed better (although not statistically significant) specificity, positive predictive value, and accuracy than early or delayed PET alone for LN staging in NSCLC [6]. Other studies also have described the advantages of DTP PET/CT for the evaluation of mediastinal LN metastasis [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in several studies, it has been proposed that dual-time-point (DTP) FDG PET/ CT may improve the accuracy of LN staging in NSCLC [6][7][8]. However, other studies reported that single-timepoint (STP) FDG PET/CT at 1 h after FDG injection was sufficiently useful for LN staging in NSCLC, and the usefulness of DTP PET/CT is still controversial [9][10][11].…”
Section: Introductionmentioning
confidence: 99%